Teachers' and Education Personnel's Perceptions of the Prototype Curriculum's Readiness for Implementation in the Academic Year 2022/2023 - Didi Franzhardi; Muhammad Kristiawan; Rambat Nur Sasongko (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The goal of this study was to find out what instructors and educators thought about the implementation of the 2022 Prototype curriculum in learning. The descriptive technique is used in this study. This study employs a population study with 19 teachers and education staff members from SMA Negeri 1 Belitang, East OKU, South Sumatra, selected using a purposive sample approach. In this study, questionnaires and interviews were utilized to collect data. The acquired data was then evaluated using descriptive statistics. According to the findings of this study, all participating teachers and education staff agree on the implementation of the Prototype curriculum 2022 in schools and recognize the benefits contained in the Prototype curriculum for 2022 which is contain character building of students.